2017
DOI: 10.1177/0218492317746252
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia as an independent predictor of adverse outcomes in pulmonary embolism

Abstract: Background The purpose of this study was to investigate the correlation between the computed tomography pulmonary artery obstruction index and parameters of functional lung impairment in acute pulmonary embolism, and establish the value of these parameters in prognosticating right ventricular dysfunction and 30-day mortality. Methods This study included 322 consecutive patients (mean age 45.6 ± 13.2 years, 46.9% male) with acute pulmonary embolism, free of other cardiopulmonary disease, who underwent computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In a series of 20 subjects free of previous cardiopulmonary disease and diagnosed with acute pulmonary embolism, McIntyre and Sasahara 14 observed a good correlation between P aO 2 and both cardiac index and the degree of pulmonary vascular obstruction measured by pulmonary angiography. Clinical studies also showed an association between hypoxemia and right-ventricular dysfunction 16,18 or elevated troponin levels, 10 both markers of the hemodynamic impact of acute pulmonary embolism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a series of 20 subjects free of previous cardiopulmonary disease and diagnosed with acute pulmonary embolism, McIntyre and Sasahara 14 observed a good correlation between P aO 2 and both cardiac index and the degree of pulmonary vascular obstruction measured by pulmonary angiography. Clinical studies also showed an association between hypoxemia and right-ventricular dysfunction 16,18 or elevated troponin levels, 10 both markers of the hemodynamic impact of acute pulmonary embolism.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical studies that investigated the relationship between hypoxemia on presentation and outcome during acute pulmonary embolism brought mixed results: most studies reported lower P aO 2 in subjects with worse outcomes in all-risk 8,16 or intermediate-risk acute pulmonary embolism 24 ; however, hypoxemia was not an independent predictor of mortality in multivariate analyses. 18 In a study that focused on factors associated with early (5 d) clinical deterioration in 298 subjects with all-risk acute pulmonary embolism, factors independently associated with a severe outcome (as defined by the occurrence of either death, advanced cardiac life support, ventricular tachycardia or fibrillation, mechanical ventilation, vasopressors, thrombolysis, or thrombectomy) were systolic blood pressure Ͻ 90 mm Hg in the emergency department, elevated Nterminal pro-brain natriuretic peptide and right-ventricular strain on echocardiogram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal and liver function may be compromised in patients with APE due to hemodynamic instability and decreased organ perfusion [30,31]. Moreover, the disturbed oxygenation may cause tissue hypoxia and further impair renal and hepatic function [32,33]. These ndings highlight the strong relationship between the MELD scores and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As time went on, patients' life safety would be threatened [4][5][6] . Niu Hongxia et al [7] indicated that, the state of pulmonary embolism is dangerous, pathogenesis is complex and clinical manifestations are not typical, so misdiagnosis and missed diagnosis cannot be avoided. The fatality rate can reach 20%-30%.…”
Section: Discussionmentioning
confidence: 99%